COVID-19 and financial performance: Pre and post effect of COVID-19 on organization performance; A study based on South Asian economy - Qadri, Syed Usman; Ma, Zhiqiang; Raza, Mohsin; Li, Mingxing; Qadri, Safwan; Ye, Chengang; Xie, Haoyang (Frontiers in Public Health, 2023)
The COVID-19 epidemic has damaged developing as well as developed economies and reduced the profitability of several companies. Technological advancement plays a vital role in the company's performance in this current situation. All activities carry on virtually. In this study, the financial performance of enterprises in the South Asian banking industry will be compared before and after the COVID-19 epidemic. Furthermore, the full influence of the pandemic will take place in the long run. This study also explains the technological effect on improving performance, especially during the period of the COVID-19 pandemic. It has an impact on people's social lives as well as the economic world. This study examined a sample of 34 banks from the South Asian region from 2016 to 2021. A Wilcox rank test was used to determine whether there was a significant difference before and after the epidemic era. The overall conclusion of this study is that the COVID-19 pandemic had a significant influence on the bank's financial performance, particularly in terms of profitability. But technological advancement has a positive effect on organizational performance, ultimately increasing the financial performance of South Asian banks. And there is a big difference between pre-pandemic and post-pandemic organizational performance. The findings of this study have significant policy implications since it is clear that cooperation among governments, banks, regulatory agencies, and central banks is necessary to address the financial and economic effects of the COVID-19 pandemic.